THE ROLE OF TECHNOLOGICAL EDUCATION IN THE PROFESSIONAL FIELD (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the role of the science of technological education in the field of professions, its importance in directing young people to the profession and its inextricable relationship with the requirements in the labor market. Also, through technological education, the ways of forming professional skills, culture of Labor, creative thinking and technical competencies in students are covered. The article analyzes the strategic tasks of technological education in the conditions of the modern economy and its integration with vocational education.